The Weak Rationality Principle in Economics - Gebhard Kirchgässner (Swiss Journal of Economics and Statistics, 2013)
The weak rationality principle is not an empirical statement but a heuristic rule for how to proceed in social sciences. It is a necessary ingredient of any 'understanding' social science in the Weberian sense. In this paper, first this principle and its role in economic theorizing are discussed. It is also explained why it makes sense to use a micro-foundation and, therefore, to employ the rationality assumption in economic models. Then, we discuss whether the anomalies of individual behaviour as highlighted in modern behavioural economics impair the applicability of the weak rationality principle. This is not the case. We conclude with some remarks on handling the problems of 'free will' as well as 'weakness of the will' within the economic approach.
Keywords: B41; 330; Rationality; Self-Interest; Micro-Foundation; Bounded Rationality